The Dynamics Of Bullying Reality In The Movie “From The Ashes”: Teun A.Van Dijk’s Critical Discourse Analysis - Nisa Nafisa A; Misbahus Surur (Center of Language and Cultural Studies, 2024)
Bullying is a social problem that often occurs, especially in educational settings. Bullying can have an impact on the victim's psychological condition, mental, physical, and emotional control. This research was conducted to describe the text structure, social cognition, and social context using Van Dijk's critical discourse analysis model in the movie “From The Ashes”. This research uses a qualitative descriptive method. The data sources are divided into primary data sources in the form of the movie “From the Ashes” and secondary data sources, in the form of supporting data from several literature sources, journals, and materials from the internet related to the topic of study. This research uses the techniques of watching, reading, and taking notes to collect data. The analysis techniques used are data reduction, data presentation, and conclusion. The results of this study are: (1) The text structure consists of macro-structure elements in the form of themes raised, namely the issue of bullying, superstructure in the form of the plot of this film, and micro-structure focusing on semantic aspects, namely setting, details, and intent. (2) Social cognition that shows the director's views regarding social discourse in the Arab educational environment related to the issue of bullying and discipline in schools. (3) Social context that brings people's views that bullying cases in the educational environment, especially among teenagers, still occur.